2003
DOI: 10.1353/ctt.2003.0019
|View full text |Cite
|
Sign up to set email alerts
|

Firearms Diffusion, Exotic and Indigenous Knowledge Systems in the Lowveld Frontier, South Eastern Zimbabwe 1870-1920

Abstract: This article considers late-nineteenth-century firearms as technology received and used by Africans with a variety of social outcomes. It focuses on the Gonarezhou area of South Eastern Zimbabwe, a rich wildlife habitat now incorporated in the Great Limpopo Transfrontier Park, the largest single wildlife conservation area in the world. When completely established it will cover 100,000 square kilometers in Zimbabwe, South Africa, and Mozambique. I treat the transfer of firearms here as a societal demand and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, at the beginning of the 1950s wildlife from the present-day LNP dispersed and populated the KNP (Pienaar et al, 1966;Whyte et al, 2003;Mavhunga and Spierenburg, 2009). Likewise, Dias and Rosinha (1971), Mavhunga andSpierenburg (2009), andMadeiros (2017), indicated that from the 1940s to 1970s about 3,000 elephants and countless species of other LH were killed in many areas in the former Rhodesian and Portuguese East Africa (present-day LNP area) as campaigns to eradicate tsetse flies and took complete refuge in safe areas of Transvaal. Sidney (1965) and Child and Savory (1964), pointed to the destruction and degradation of habitat as the prime reason for the decline in the number of LH in the middle of the nineteenth century in all of southern Africa.…”
Section: The Peak Of the Colonial Period-reference For Near-natural A...mentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, at the beginning of the 1950s wildlife from the present-day LNP dispersed and populated the KNP (Pienaar et al, 1966;Whyte et al, 2003;Mavhunga and Spierenburg, 2009). Likewise, Dias and Rosinha (1971), Mavhunga andSpierenburg (2009), andMadeiros (2017), indicated that from the 1940s to 1970s about 3,000 elephants and countless species of other LH were killed in many areas in the former Rhodesian and Portuguese East Africa (present-day LNP area) as campaigns to eradicate tsetse flies and took complete refuge in safe areas of Transvaal. Sidney (1965) and Child and Savory (1964), pointed to the destruction and degradation of habitat as the prime reason for the decline in the number of LH in the middle of the nineteenth century in all of southern Africa.…”
Section: The Peak Of the Colonial Period-reference For Near-natural A...mentioning
confidence: 96%
“…The area was affected by Mozambique's civil war from 1976 to 1992 (Hatton et al, 2001) and decades of poaching, which decimated the populations of almost all LH species (Hofmeyr, 2004;Lunstrum, 2016). Patterns of wildlife distribution and movements in the current LNP from mid to late nineteenth century were shaped by tsetse fly expansion, excessive off-take of ivory, systematic expansion of sport hunting, demarcation of colonial borders, and Rinderpest (Martinho, 1934;Mavhunga, 2003;Mavhunga and Spierenburg, 2009). In the early twentieth century, LH populations were massively culled by veterinary services in former Rhodesia and Portuguese East Africa (present-day Mozambique) to prevent livestock diseases caused by ticks, Rinderpest, and tsetse fly (Martinho, 1934;Madeiros, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If viewed purposively, this spread can be described as both organizational learning and knowledge management (Sabet and Klingner, 1993). If viewed descriptively, innovation diffusion and adoption includes the intended and unintended consequences of complex and symbiotic relationships between producers and consumers that occur across organizations (Schrage, 2004), countries (Beatty, 2003) and regions (Mavhunga, 2003).…”
Section: Innovation Diffusion and Adoptionmentioning
confidence: 99%
“…Moreover, because economic development models focus on top‐down relationships between IFIs and recipient country governments and emphasize the key role of “star power” economists as international change agents, these models are somewhat at variance with more generally accepted models of effective technology transfer and sustainable development. In fact, technology transfer is reciprocal (Klingner and Sabet 2005; Mavhunga 2003), recipients play a key role in the innovation diffusion and adoption process (Schrage 2004), and Africans are the ones primarily responsible for acting in their own interests and making decisions about their own future (Mkandawire 2006).…”
Section: Disciplinary: the Preeminence Of Economicsmentioning
confidence: 99%